The American Pageant / A History of the Republic; Volume I - Bailey Thomas A.; Kennedy David M (D.C. Heath And Company, 1983)
New World Beginnings, Completing the Thirteen Colonies, The Duel for North America, The Road to Revolution, America Secedes from the Empire, Federalists and Foreign Fiction, The Triumph of Jeffersonian Democracy, The Rise of Jacksonian Democracy, Manifest Destiny in the Forties, Creating an American Character - 1790-1860, The South and the Slavery Controversy, The War for Southern Independence, Behind the Lines: North and South, The Ordeal of Reconstruction, Appendix, Color Portfolio, Index.
New World Beginnings, Completing the Thirteen Colonies, The Duel for North America, The Road to Revolution, America Secedes from the Empire, Federalists and Foreign Fiction, The Triumph of Jeffersonian Democracy, The Rise of Jacksonian Democracy, Manifest Destiny in the Forties, Creating an American Character - 1790-1860, The South and the Slavery Controversy, The War for Southern Independence, Behind the Lines: North and South, The Ordeal of Reconstruction, Appendix, Color Portfolio, Index.